Bouveret's Syndrome: Diagnostic Dilemmas and Therapeutic Strategies - A Comprehensive Educational Approach for Healthcare Professionals - Paweł Dąda; Paweł Pawlik; Przemysław Zaroda; Patrycja Niewinna; Michał Żuchowski; Dominika Mańdziuk; Klaudia Kołodziej; Wojciech Kołodziej; Jakub Wawrzkowicz; Monika Korga (Kazimierz Wielki University, 2024)
Bouveret's syndrome, a rare complication of gallstone disease, poses a significant diagnostic and therapeutic challenge, particularly in elderly individuals with multiple comorbidities. The mortality rate ranges from 12-30%, emphasizing the importance of prompt and accurate diagnosis. Nonspecific symptoms, such as nausea, vomiting, and abdominal pain, contribute to delayed diagnosis. Healthcare professionals, especially those involved in gastroenterology and surgery, require comprehensive education on Bouveret's syndrome. Training should emphasize the diverse diagnostic modalities, including the use of imaging techniques such as X-rays, ultrasound, and MRI. Awareness of the syndrome's rarity and collaboration among specialists from various fields are crucial for effective management. Additionally, educational programs should underscore the need for individualized treatment plans, considering patient parameters such as age, comorbidities, and the inflammatory state of surrounding tissues. While endoscopic procedures exhibit lower success rates, they are often preferred due to the high risk associated with open surgical procedures in elderly patients. Continuous medical education should also highlight the potential link between diabetes and Bouveret's syndrome, emphasizing the importance of recognizing risk factors and ensuring timely medical intervention. In conclusion, enhancing the knowledge base of healthcare professionals through targeted education is essential for improving the diagnosis and management of Bouveret's syndrome, ultimately contributing to better patient outcomes.